2022
DOI: 10.1186/s12998-022-00467-9
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity promotion in chiropractic: a systematic review of clinician-based surveys

Abstract: Background Physical inactivity is a global health pandemic. Allied healthcare providers, including chiropractors, are well placed to integrate individual physical activity (PA) promotion into routine care. A previous systematic review identified that approximately 90% of chiropractors held a positive opinion towards healthier patient lifestyles; however, the extent to which chiropractors promote PA to their patients within routine care is unclear. This systematic review aimed to describe chirop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…For instance, the post-2015 American College of Sports Medicine questionnaire now primarily screens the individual’s current PA level [ 20 ]. As chiropractors knowingly obtain PA information from patients [ 15 ], implementing tools like the validated General Practice Physical Activity Questionnaire (GPPAQ) can enhance the screening process [ 21 ]. The GPPAQ can briefly assess PA levels in routine practice, grouping patients into inactive-to-active categories that can be easily conveyed to patients [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the post-2015 American College of Sports Medicine questionnaire now primarily screens the individual’s current PA level [ 20 ]. As chiropractors knowingly obtain PA information from patients [ 15 ], implementing tools like the validated General Practice Physical Activity Questionnaire (GPPAQ) can enhance the screening process [ 21 ]. The GPPAQ can briefly assess PA levels in routine practice, grouping patients into inactive-to-active categories that can be easily conveyed to patients [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found chiropractors recognise the importance of PA promotion and are prepared to routinely discuss and/or counsel patients on this health topic [ 15 ]. Additionally, previous research has shown that 85% of Australian chiropractors report often discussing PA as part of their patient management [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the post-2015 American College of Sports Medicine questionnaire now primarily screens the individual's current PA level [19]. As chiropractors knowingly obtain PA information from patients [15], implementing tools like the validated General Practice Physical Activity Questionnaire (GPPAQ) can enhance the screening process [20]. The GPPAQ can brie y assess PA levels in routine practice, grouping patients into inactive-to-active categories and easily conveyed to patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found chiropractors recognise the importance of PA promotion and are prepared to routinely discuss and/or counsel patients on this health topic [15]. Additionally, previous research has shown that 85% of Australian chiropractors report often discussing PA as part of their patient management [16].…”
Section: Introductionmentioning
confidence: 99%